Geographical perspectives (London, 1985)
This is the best and most comprehensive textbook on Latin American geography available at the moment. It treatment of standard geographical topics is sound and it offers an excellent background to the newcomer to Latin American studies whether geographer or economicst, anthropologist or geologist. As such the book will be welcomed by all those with an interest Latin America and particularly by those involved in introducing undergraduates to the study of the region
Keywords: Latin america; Description